Evaluación del comportamiento en pos cosecha de papanabo (Brasica papa) con tres tipos de atmósfera y tres temperaturas de almacenamiento en la provincia de Cotopaxi - Toapanta Sinchiguano, Fernanda del Pilar (2013)
The turnip is a highly nutritious vegetable that helps in the metabolism of human and is gaining market nationally and internationally, for this reason it has done the following research topic “Evaluation of behaviorpost harvest of turnip (Brassica rapa) with three types of modified atmospheres and three storage temperatures in the Cotopaxi Province”, with the following specific objectives: To determine the best atmosphere, the best temperature for the permanence in storing `turnip. Perform the economic analysis. Laboratory research was conducted at temperatures of 4 ° C, 8 ° C and ambient temperature of 22 º C, in this investigation, a split plot design was used, with nine treatments and three replications, test was applied Tukey (5%) indicators to evaluate were: Incidence of pests, diseases and physiological disorders, loss of weight (y), acidity, soluble solids (o Brix), Fruit firmness (lbfxcm2-1), the management of experiment consisted of: Harvest turnip, sheet separation, washing, heavy root and record their weights, air drying, shape and distribution of the experimental units, and the latest storage in different temperatures